Reformation in Egypt’s Cotton Programme Towards Upland Cotton: Barbadense vs Hirsutum - NEGM, MOHAMED (Cotton Research Journal, 2021)
As the leading agricultural sub-sector in Egypt, Cotton provides the livelihoods for hundreds of thousands of farm families. The cotton sub-sector, including production, trading, ginning, spinning, textile manufacturing, oil extraction, and livestock feed manufacturing, is the leading employer in the country. The development of new Barbadense varieties requires a well-organized team operating over a very long period, generally between 15-18 years. There has been considerable interest in the past to exploit the potential of Hirsutum varieties in Egypt. In the early 1980s and before, Egyptian scientists in Cotton Research Institute (CRI), in universities and other research centers, conducted production trials of Hirsutum varieties. With proper regulations regarding the cultivation of these two types of cotton, along with regulations that are already in place and enforced by the Ministry of Agriculture, Egypt should be able to produce and profit from both types of cotton. Local production of American Upland cotton in Upper Egypt will be spun into coarse and medium yarn counts and is a potential substitute for imported raw Upland cotton and yarns, and Egyptian Long and Extra-Long Staple in North Delta will be used for the production of fine yarns and fabrics for export.